2010
DOI: 10.1080/14613801003746550
|View full text |Cite
|
Sign up to set email alerts
|

Institutional culture and learning I: perceptions of the learning environment and musicians' attitudes to learning

Abstract: Research in higher education has established a relationship between student approaches to learning and their perceptions of the learning environment. This study aims to make a contribution to music education literature by investigating undergraduate music students' perceptions of the learning context and their attitudes towards learning and performance. The research design included a large questionnaire survey followed up by 13 case study interviews and six focus groups. Survey participants were 170 undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Conclusions and implications for education arising from the two 'institutional culture and learning' papers Overall, findings reported in the two 'institutional culture and learning' papers (Papageorgi et al 2010b; current paper) support that the context where music performance learning takes place and the institutional culture relates to students' perceptions and approaches to learning and performance. This is in line with research in other higher education settings suggesting that perceptions of the learning environment influence students' approaches to studying (Lizzio, Wilson, and Simons 2002).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Conclusions and implications for education arising from the two 'institutional culture and learning' papers Overall, findings reported in the two 'institutional culture and learning' papers (Papageorgi et al 2010b; current paper) support that the context where music performance learning takes place and the institutional culture relates to students' perceptions and approaches to learning and performance. This is in line with research in other higher education settings suggesting that perceptions of the learning environment influence students' approaches to studying (Lizzio, Wilson, and Simons 2002).…”
Section: Discussionsupporting
confidence: 58%
“…Findings discussed in Papageorgi et al (2010b), suggested that they felt they had less control over coping skills for managing stage fright and everyday stress, as well as stamina, which could explain this finding. No differences between students were found in relation to group performance, suggesting that when they had support from coperformers they felt equally confident.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations